The Pancasila in the Age of Digital Society 5.0: Indonesia Legal System Perspective: Pancasila di Era Masyarakat Digital 5.0: Perpspektif Sistem Hukum Indonesia - Desinta, Desinta Dwi Rapita (Indonesian Journal of Law and Economics Review, 2024)
his study explores the transformative impact of the digital era, specifically Society 5.0, on the Indonesian legal system, focusing on the incorporation of Pancasila values as a universal ethical foundation. Adopting a normative legal research method with a conceptual approach, the study analyzes how the Indonesian legal system, predominantly influenced by the civil law system, adapts to the challenges posed by technological advancements and the emerging digital society. The research reveals that Indonesia's unique legal system, grounded in Pancasila, exhibits characteristics of religiosity, humanism, and social justice, enabling it to adapt to societal changes while maintaining core national values. The digital transformation, embodied in Society 5.0, necessitates a legal framework that balances economic development with social problem-solving through innovative and sustainable technology integration. The study highlights the increasing significance of cybersecurity awareness and the potential recognition of artificial intelligence as a new legal subject. Emphasizing the role of Pancasila's ethical principles, the study concludes that a consistent application of these values is crucial for developing a responsive legal system capable of addressing the complexities of a digital society. This alignment ensures that legal evolution aligns with societal aspirations, maintaining harmony and order within the framework of a rapidly evolving digital landscape. The findings underscore the importance of legal reform in legislative, human resources, institutional, and cultural aspects, advocating for a harmonized approach between technological advancements and existing or forthcoming regulations, guided by Pancasila's values.Highlights: Pancasila as Ethical Guide: Emphasizes Pancasila's pivotal role in shaping Indonesia's legal responses to digital challenges. Legal System's Digital Adaptation: Highlights the Indonesian legal system's evolution in the face of advancing digital technologies. Harmonized Legal Reforms: Stresses the need for sustainable legal reforms aligned with societal values in the digital era. Keywords: Society 5.0, Pancasila, Indonesian Legal System, Digital Transformation, Cybersecurity